2017
DOI: 10.1007/s11940-017-0441-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Thalamic Stroke

Abstract: The thalamus plays an important role in different brain functions including memory, emotions, sleep-wake cycle, executive functions, mediating general cortical alerting responses, processing of sensory (including taste, somatosensory, visual, and auditory) information and relaying it to the cortex, and sensorimotor control. Thalamic stroke, both in isolation and in combination with infarcts involving other structures, are not rare. The functional complexity of the thalami nuclei and the not uncommon normal var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 45 publications
0
38
0
Order By: Relevance
“…In contrast to arterial infarcts, the observed signal abnormality is primarily due to venous congestion and resultant vasogenic oedema, rather than cytotoxic oedema. The lesions are characteristically bilateral, however strikingly asymmetric in some cases [ 60 ].
Fig.
…”
Section: Pathology Predominantly Affecting the Thalamimentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to arterial infarcts, the observed signal abnormality is primarily due to venous congestion and resultant vasogenic oedema, rather than cytotoxic oedema. The lesions are characteristically bilateral, however strikingly asymmetric in some cases [ 60 ].
Fig.
…”
Section: Pathology Predominantly Affecting the Thalamimentioning
confidence: 99%
“…It has been recently found that bilateral thalamic gliomas, in contrast to their unilateral counterparts, frequently harbour mutations in EGFR oncogene, while H3K27M mutants are actually rare. Additionally, genomically tailored therapy (with tyrosine kinase inhibitors) showed encouraging results in a few paediatric patients with such bithalamic neoplasms [ 60 , 64 ].…”
Section: Pathology Predominantly Affecting the Thalamimentioning
confidence: 99%
“…As such, insults affecting the thalamus have the potential to impact many different areas of function and cause a diverse set of deficits. The vascular supply of the thalamus includes four main arteries: the polar (tuberothalamic) artery, the inferolateral (thalamogeniculate) artery, the paramedian (thalamosubthalamic) artery, and the posterior choroidal arteries [ 2 , 12 ]. There is considerable variation in the territory supplied by each artery.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic strokes in more common locations, such as the middle cerebral artery, most often produce predictable focal neurological deficits and clinical syndromes. In contrast, the presentations of someone with an AOP infarct include altered mental status, coma, transient or episodic loss of consciousness, memory impairment, psychosis, aphasia, dysarthria, and oculomotor dysfunction [ 2 - 9 ]. When there is an acute stroke in the AOP territory, the diagnosis is often missed due to the unusual presenting symptoms and signs, as well as the fact that it may not be visualized on primary imaging.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Thalamic stroke is not rare, accounting for 11% of posterior circulation infarcts. [9] The thalamus plays a critical role in supporting cognitive and motor functions, managing our sensitivity to temperature, light, pain, and physical touch. It controls the flow of visual, auditory, and motor information, being also involved in different aspects of learning, memory, speech, language understanding, emotions, motivation, attention, and wakefulness, being in charge of our sense of balance and awareness of our arms and legs.…”
Section: Introductionmentioning
confidence: 99%